PEGylation and its impact on the design of new protein-based medicines. (October 2014) - Ginn, Claire; Khalili, Hanieh; Lever, Rebecca; Brocchini, Steve
PEGylation is the covalent conjugation of PEG to therapeutic molecules. Protein PEGylation is a clinically proven approach for extending the circulation half-life and reducing the immunogenicity of protein therapeutics. Most clinically used PEGylated proteins are heterogeneous mixtures of PEG positional isomers conjugated to different residues on the protein main chain. Current research is focused to reduce product heterogeneity and to preserve bioactivity. Recent advances and possible future directions in PEGylation are described in this review. So far protein PEGylation has yielded more than 10 marketed products and in view of the lack of equally successful alternatives to extend the circulation half-life of proteins, PEGylation will still play a major role in drug delivery for many years to come.